Pengaruh Kualitas Lingkungan dan Motivasi pada Kinerja Akademik Siswa SMA - Yudhistira Kusuma; Hanson Endra Kusuma; Angela Christysonia Tampubolon; Tutin Aryanti (RUAS (Review of Urbanism and Architectural Studies), 2018)
Environment (external factors) and user attributes (internal factors) affect the user's response to the environment. This study aims to uncover how the quality of the environment in high school as an external factor and student motivation as an internal factor affects the academic performance of the students. The research was conducted with qualitative and quantitative approach. Data were collected by survey using an online questionnaire. From the regression analysis, it was found that the dimensions of external factors of "classroom order", "social interaction and supervision" and "air quality" further increased the effectiveness of student learning rather than internal dimensions of "resilience and capacity building". Meanwhile, the decrease in air quality, noise, and environmental pollution can cause student learning disruption. Based on these findings, it can be concluded that the learning environment plays an important role in shaping the effectiveness of student learning.